Co-Movements in Long-Term Interest Rates and the Role of PPP-Based Exchange Rate Expectations - Knot, Klaas (IMF Working Papers; Working Paper ;, 1999)
This paper investigates international co-movement in bond yields by testing for uncovered interest parity (UIP). Existing work is supplemented by focusing on long instead of short-term interest rates and by employing exchange rate expectations derived from purchasing power parity (PPP) instead of actual outcomes. Among the major currencies during 1975-97, the paper does not find a further increase in co-movement beyond that associated with the wave of financial market liberalization in the early 1980s. Given the similarity between PPP-based UIP tests and those employing actual exchange rate outcomes, the value added of the former lies mainly with data availability.